Dakwah dan Sepak Bola: Upaya Qatar Membaca Peluang Dakwah Saat Piala Dunia 2022 - Putra, Afif Pradana; Hidayat, Imam Alif (UIN Sunan Ampel Surabaya, 2023)
This study is about how Qatar reads Da'wah opportunities at the 2022 World Cup in building an Islam full of love and mercy, namely through three ways: da'wah bilhal, da'wah bil lisan, and da'wah bil qalam. Through its descriptive analysis approach, while the data is based on several online information media. The result of this study is that Qatar is trying to introduce to the whole world that Islam is not a religion that teaches violence, but that Islam is a religion that always upholds compassion for all tribes, nations, and countries, even in differences in skin color, which is reflected in the opening of the 2022 World Cup. The values of da'wah conveyed in this series of events prove that there is an active and conducive da'wah, always upholding the values of love and mercy. The da'wah carried out by Qatar shows the da'wah carried out by the Prophet, such as honoring guests, providing maximum service to hotel facilities, and all other things that are found throughout the Qatar region.